Accelerated biodegradation of iron-based implants via tantalum-implanted surface nanostructures - Min-Kyu Lee; Hyun Lee; Cheonil Park; In-Gu Kang; Jinyoung Kim; Hyoun-Ee Kim; Hyun-Do Jung; Tae-Sik Jang (Bioactive Materials, 2022)
In recent years, pure iron (Fe) has attracted significant attention as a promising biodegradable orthopedic implant material due to its excellent mechanical and biological properties. However, in physiological conditions, Fe has an extremely slow degradation rate with localized and irregular degradation, which is problematic for practical applications. In this study, we developed a novel combination of a nanostructured surface topography and galvanic reaction to achieve uniform and accelerated degradation of an Fe implant. The target-ion induced plasma sputtering (TIPS) technique was applied on the Fe implant to introduce biologically compatible and electrochemically noble tantalum (Ta) onto its surface and develop surface nano-galvanic couples. Electrochemical tests revealed that the uniformly distributed nano-galvanic corrosion cells of the TIPS-treated sample (nano Ta–Fe) led to relatively uniform and accelerated surface degradation compared to that of bare Fe. Furthermore, the mechanical properties of nano Ta–Fe remained almost constant during a long-term in vitro immersion test (~40 weeks). Biocompatibility was also assessed on surfaces of bare Fe and nano Ta–Fe using in vitro osteoblast responses through direct and indirect contact assays and an in vivo rabbit femur medullary cavity implantation model. The results revealed that nano Ta–Fe not only enhanced cell adhesion and spreading on its surface, but also exhibited no signs of cellular or tissue toxicity. These results demonstrate the immense potential of Ta-implanted surface nanostructures as an effective solution for the practical application of Fe-based orthopedic implants, ensuring long-term biosafety and clinical efficacy.